Foucault, Platón y la historia de la verdad - Díaz Marsá, Marco A. (Logos. Anales del Seminario de Metafísica, 2007)
Following on the concept of “a history of the truth” by de late Foucault, we will look into the Frenchman´s mind and attempt to pursue and analyse the significance of the platonic movement in relation to such history. This way, it will be necessary to show how the genealogy of the modernsubject of the truth (in both meaning of the expression that refers so much to the assujettissement of hte subject of the knowledge through the technê, like the subjectivation partly independent of an ethic subject of the truth, with a critical-aesthetic character) has to return back to Plato to find there certain decisive elements for the comprehension of our history, in which certain relationships amongst the “power, the truth, and the subject matter have shown themselves as determinants agents, givind room to a double game of the objectivity and subjectitivity, of domination and freedom that marks our World.